Incidental findings in patients evaluated with cone beam computed tomography for orthodontic treatment - FLAIBAN,Everton (2017)
ABSTRACT Objective: The aim of this retrospective study was to determine and quantify incidental findings in CBCT scans taken exclusively for orthodontic purposes. Methods: A total of 202 scans were evaluated by two examiners and classified into five different groups. Results: A total of 227 incidental findings were found in a sample of patients aged 5-58 years old. The highest number of findings was of dental origin (n = 157), followed by airway (N = 46), skull (N = 16) and ATM (n = 8). Scans with no incidental finding accounted for 20% of the examinations. Subjects having lower mean age were found in the group of airway findings. The prevalence of incidental findings in the current study was consistent with the literature, thus corroborating their high frequency. Orthodontists who make use of CBCT are responsible for assessment of all data. Conclusion: The precise evaluation of incidental findings may help in the early diagnosis, treatment and patient monitoring. Further studies should be conducted to assess the influence of these findings on the orthodontic treatment.